Investigation of Modal Behaviour of Resonance Spruce Wood Samples (Picea abies L.) - MANIA, Przemysław; FABISIAK, Ewa; SKRODZKA, Ewa (Archives of Acoustics, 2017)
Results of experimental modal analysis of a resonance and non-resonance spruce wood (Picea abies L.) are presented. The resonance wood came from a tree from Poland and Bosnia and Herzegovina, while the non-resonance wood came from the vicinity of Olsztyn from the north-eastern Poland. The modal parameters (modal frequency, modal damping and mode shapes) of the wood samples were determined for the samples of 8 mm in thickness. Modal analysis was made by pulse excitation. The resonance and non-resonance wood differ in the fundamental modal parameters as well as in the number of potential modes. Additionally, calculated values of damping factor are presented. The values are much bigger for a non-resonance wood than for good quality resonance spruce.